Risk Assessment and Hazard Mapping - Sagara, Junko (World Bank, Washington, DC, 2013)
Hazard and risk assessments are the crucial first step in disaster risk management (DRM) and the basis for formulating DRM policies. They must take into account worst-case scenarios in the event of the largest possible hazard, while recognizing that hazard assessments of earthquakes and tsunamis will always have their limitations and associated uncertainties. In Japan so-called hazard maps, that combine hazard information with evacuation routes and locations of evacuation centers, are effective tools for promoting evacuation procedures and risk awareness among the public. However, in the case of the Great East Japan Earthquake (GEJE), these hazard maps, created before the event, may have given people a false sense of security by underestimating the disaster's potential impact. Hazard maps should be designed to guide and facilitate prompt evacuation. They should be easy to understand and readily available. This report gives findings; lessons; and recommendations for developing countries.